Muslim physicians and palliative care: attitudes towards the use of palliative sedation - Muishout, George (Support Care Cancer, 2018)
BACKGROUND: Muslim norms concerning palliative sedation can differ from secular and non-Muslim perceptions. Muslim physicians working in a Western environment are expected to administer palliative sedation when medically indicated. Therefore, they can experience tension between religious and medical norms. OBJECTIVE: To gain insight into the professional experiences of Muslim physicians with palliative sedation in terms of religious and professional norms. DESIGN: Interpretative phenomenological study using semi-structured interviews to take a closer look at the experiences of Muslim physicians with palliative sedation. Data were recorded, transcribed and analysed by means of interpretative phenomenological analysis (IPA). PARTICIPANTS: Ten Muslim physicians, working in the Netherlands, with professional experience of palliative sedation. RESULTS: Two main themes were identified: professional self-concept and attitudes towards death and dying. Participants emphasized their professional responsibility when making treatment decisions, even when these contravened the prevalent views of Islamic scholars. Almost all of them expressed the moral obligation to fight their patients’ pain in the final stage of life. Absence of acceleration of death was considered a prerequisite for using palliative sedation by most participants. CONCLUSIONS: Although the application of palliative sedation caused friction with their personal religious conceptions on a good death, participants followed a comfort-oriented care approach corresponding to professional medical standards. All of them adopted efficient strategies for handling of palliative sedation morally and professionally. The results of this research can contribute to and provide a basis for the emergence of new, applied Islamic ethics regarding palliative sedation.